Rekonstruksi Laporan Keuangan Berbasis Nirlaba Berdasarkan ISAK Nomor 35 : Studi Kasus Masjid Darussalikin Bangsalsari - M. Dimas Alfansyah K; Norita Citra Yuliarti; Ari Sita Nastiti (CV. Ulil Albab Corp, 2023)
The purpose of this study is to find out how the application of the accounting system implemented by the Darussalikin Mosque in Krajan Hamlet RT/RW 001/012, Karangsono Village, Bangsalsari District, Jember Regency. The method used in this study is a qualitative method with an esscriptive approach. This study used two types of data, namely primary data and secondary data with observational data collection techniques, interviews, documentation and literature studies. The results of this study show that Darussalikin Mosque in making financial statements has not applied based on the Inter-Performance of Financial Accounting Standards Number 35 (ISAK Number 35), which includes notes to financial statements, comprehensive income statements, statements of financial position, statements of cash flows, and statements of net assets. The recording that has been done so far is still manual and simple. The media is to provide reports to the public by conveying the results of income and expenditure on Friday before the Friday sermon to carry out the sermon.